SSUES AND CHALLENGES IN TEACHING ACADEMIC WRIITNG TO NON-NATIVE ENGLISH SPEAKERS: THE CASE OF HSE - Vera A. Dugartsyrenova (Высшее образование в России)
This paper examines some of the current issues and challenges of teaching academic writing to non-native speakers of English faced by Russian institutions within the current education paradigm. The findings are drawn from an analysis of samples of scientific works (project proposals) produced by 4th year students at the National Research University - Higher School of Economics. The paper offers an interpretation of what underlies the challenges and some possible solutions to the issues discussed.